955,000 (Vancouver : Vancouver Art Gallery, 1970)
Acconci, Vito ; Andre, Carl ; Arnatt, Keith ; Artschwager, Richard ; Atkinson, Terry ; Baldessari, John ; Baldwin, Maichael ; Barry, Robert ; Barthelme, Rick ; Beery, Gene ; Bochner, Mel ; Bollinger, Bill ; Borofsky, Jonathan ; Burgy, Donald ; Buren, Daniel ; Castoro, Rosemarie ; Curnoe, Greg ; Darboven, Hanne ; de Maria, Walter ; Dibbets, Jan ; Dikeakos, Christos ; Ferrer, Rafael ; Graham, Dan ; Haacke, Hans ; Hay, Alex ; Heizer, Michael ; Hesse, Eva ; Huebler, Douglas ; Huot, Robert ; Kaltenbach, Stephen ; Kawara, On ; Kienholz, Edward ; Kinmont, Robert ; Kosuth, Joseph ; Kozlov, Christine ; Latham, John ; Le Va, Barry ; LeWitt, Sol ; Louw, Roelof ; Lunden, Duane ; McLean, Bruce ; Morris, Robert ; Nauman, Bruce ; Co., N.E. Thing ; Nikolaidis, George ; Workshop, N.Y. Graphic ; Oppenheim, Dennis ; Perreault, John ; Piper, Adrian ; Rohm, Robert ; Ruppersberg, Allen ; Ryman, Robert ; Ruscha, Ed ; Sandback, Fred ; Sawchuk, George ; Serra, Richard ; Sims, Randy ; Smithson, Robert ; Sonnier, Keith ; Wall, Jeff ; Weiner, Lawrence ; Wilson, Ian
955,000, Vancouver Art Gallery, Vancouver, January 13 to February 8, 1970
kunstcatalogus